Durability testing of coconut shell according to ENV 807 - Jermer, Jöran; Wong, Andrew H.H; Segerholm, Kristoffer; Nilsson, Thomas (IRGWP, 2015)
Coconut shell was tested in the laboratory according to the European standard ENV 807 with three different soil types: compost soil, brown rot/soft rot rich soil and white rot/soft rot rich soil. Mass losses between 14 and 16 % were achieved with all three soils, indicating that the decay type is of little importance in the degradation process. Somewhat higher mass losses, 19-22 % were obtained for the durable/moderately durable, according to EN 350-2, wood species Sipo (Entandrophragma utile), whereas preservative-treated references had significantly lower mass losses, 0.5-7 %. The results of the test were promising but further experiments and testing will be necessary to explore the full potential for coconut shell to be used e.g. for composite materials with enhanced durability against decay fungi.